Metode Pembelajaran dalam Pendidikan Islam - Musthofa, Musthofa; Illahi, Nur (Tarqiyatuna: Jurnal Pendidikan Agama Islam dan Madrasah Ibtidaiyah, 2023)
The Islamic religious education method is a strategy in achieving educational learning objectives based on Islamic religious teachings. One of the goals of Islamic religious education is to form a perfect human character (insan kamil). However, along with the progress of the times, the goals of Islamic education are also increasingly complex. Islamic religious education in the current era, must be used as a way to achieve happiness in the world, including through the learning process carried out by teachers in schools. Methods in Islamic education in the current era also have an important role to maximize the competence of students in the learning process.